2020
DOI: 10.1088/2515-7639/ab7cb9
|View full text |Cite
|
Sign up to set email alerts
|

Recent advance of carbon dots in bio-related applications

Abstract: Carbon dots (CDs) is a kind of carbon nanoparticles with a plentiful of surface functional groups and tunable emission with different excitation wavelength. Broadly speaking, CDs include carbon nanodots, carbon quantum dots, graphene quantum dots, carbonized polymer dots. Due to the unique nature, they are explored for various applications in the bio-related fields such as bioimaging, sensor for ion and (bio)molecules, catalyst, LED and other fields. They are viewed as great alternative tracers to the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 183 publications
(214 reference statements)
2
31
0
Order By: Relevance
“…By discovering carbon-nano dots in the last decade, Xu et al [6] have introduced the novel fluorescent nanomaterials that have been widely used in the various research field such as in chemical sensing [10,[12][13][14][15], biology [16], nanomedicine [17,18], and photocatalysis [19]. This research group in 2004 isolated novel nanomaterial during the electrophoretic purification process of single-walled carbon nanotubes (SWCNTs) by the arc-discharge technique [6].…”
Section: Methods For Preparation Of Carbon Quantum Dotsmentioning
confidence: 99%
“…By discovering carbon-nano dots in the last decade, Xu et al [6] have introduced the novel fluorescent nanomaterials that have been widely used in the various research field such as in chemical sensing [10,[12][13][14][15], biology [16], nanomedicine [17,18], and photocatalysis [19]. This research group in 2004 isolated novel nanomaterial during the electrophoretic purification process of single-walled carbon nanotubes (SWCNTs) by the arc-discharge technique [6].…”
Section: Methods For Preparation Of Carbon Quantum Dotsmentioning
confidence: 99%
“…For the achievement of higher biocompatibility, surface passivation of CDs can be improved, which may result into the reduction in their photoluminescence intensity, and vice versa. Despite these issues, it is still unclear how CDs function as the excellent fluorophores for serving various health care applications [59,60].…”
Section: Strategies For Cds Synthesismentioning
confidence: 99%
“…CDs as the potent imaging agents play a pivotal role in the real-time imagining of either certain cells, tissues, organs, or in combination, that help in the accurate diagnosis of various forms of cancer and several diseases. Moreover, they have the tendency to efficiently deliver genes/drugs by serving as nanocarriers, as well as also being highly capable theranostic agents for various phototherapies like photodynamic and photothermal therapies [43,44,[58][59][60][61][62][63]. Henceforth, all these significant attributes of CDs make them strong foundations for serving various diagnostic and therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating various fluorescent carbon dots into scaffold endow higher surface area, tunable physicochemical, optical, and mechanical property, high stability and stimulating the biodegradation activities, and increasing biological interactions providing promising results in tissue engineering application [ 26 , 45 , 49 ]. In recent years, many reviews based on CDs have been reported in the research field, demonstrating different synthetic approaches, sensors, electronic and bioimaging applications [ 44 , 47 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. However, very few reports are available to elucidate the versatility of CDs in non-invasive tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%